Mindfulness for educational practice : a path to resilience for challenging work - Gates, Gordon S. (Emerald Publishing Limited : Information Age Publishing, 2015)
This book is the 8th Volume in the Research on Stress and Coping in Education Series. Mindfulness is gaining attention within many disciplines including education and the authors present original research and current theory for examining ways such practice can be used to improve school outcomes for students and strengthen supports for teachers and school leaders. The chapters are written to be useful for practitioners and pre-service educators by posing recommendations for those considering these strategies and techniques. Specific treatment is given to work of teachers, principals, and superintendents.Research is beginning to document the acceptability and efficacy of mindfulness-based interventions (MBIs) in the reduction of stress and burnout, and in the improvement of occupational health and well-being, among educators and school administrators. In this groundbreaking volume of the Research on Stress and Coping in Education series - Mindfulness for Educational Practice: A Path to Resilience for Challenging Work, educational researchers and practitioners advance the exploration of MBIs in educational settings by asking how they might contribute not only to stress reduction and resilience enhancement, but also to the improvement of relationships and the everyday practices of leadership, teaching and learning in the schools. Individual chapters in this volume focus on key questions in the field of study concerned with mindfulness in education today, including (1) What is the role of MBIs in enhancing emotional self-awareness and self-care in teachers, as well as their sense of efficacy and agency with regard to making broader educational changes? (2) Can mindfulness training; by enhancing attentiveness to counterfactual or novel information, as well as environmental conditions and other people's perspectives more generally, benefit educational leaders in their work in guiding their staffs towards collaborative educational reforms? (3) Can the cultivation of emotional awareness and emotion regulation skills (e.g., non-reactivity) through mindfulness training help educators - from pre-service teachers to superintendents, to improve their interpersonal skills with students, families and community members? (4) In classroom settings, can the cultivation of mindfulness and compassion in teachers promote closer teacher-student relationships and greater student engagement in learning academic subjects like math? These are the timely and important pragmatic questions addressed theoretically, empirically, and practically in this volume.The collective chapters in this volume, drawn largely from the experience of practitioners working in the schools everyday, are characterized by qualitative and action research methods and phenomenological reports of educators as they embark on a process of professional development through mindfulness training. As such, the volume marks a significant contribution in terms of documenting the perspectives, challenges, and triumphs educators are currently experiencing as they engage with MBIs in education both within and beyond the mindfulness-training context. The book is an excellent read and an important one for all those interested in research on mindfulness in education today.
Keywords: Teachers -- Job stress.; Stress in children.; Stress (Psychology) -- Prevention.; Educational psychology.; Education -- Teaching -- General.; Teaching staff.; Teaching skills and techniques.; elektronické knihy; electronic books